KEWAJIBAN PEMIMPIN DAN RAKYAT DALAM PERSPEKTIF AL-QUR;AN SURAH AN-NISA AYAT 58-59 - Zahra, Inas Afifah; Marno, Marno; Wibawa, Basuki (Journal of Islamic Education Studies, 2022)
The Qur'an is a guideline that must be implemented by anyone, namely Muslims. Especially for a leader so that his leadership is able to bring prosperity to his people and peace to his country. Surah An-nisa Verses 56 to 59 can be a reference for a leader in the one he leads. The purpose of this study is to determine the obligations of leaders and the people contained in the letter An- Nisa verses 58-59, as well as recommendations to apply them in the life of society and state. The methodology of this study is descriptive qualitative with literature research (literature) which is compiled using the concepts of Tafsir Tahlili, Tafsir Maudhu'I, and Interpretive. The results showed that the leader's obligation to the people was divided into five aspects, namely; responsibility, sacrifice, hard work, service, and exemplary. Meanwhile, the people's obligations to the leader are divided into five aspects, namely; sincere and praying, respecting and glorifying, listening and obeying, delivering advice and reminding, defending and helping. As for the wisdom of the obligations of the leader and the people in the perspective of the letter An-Nisa verses 58- 59 in the group into four parts, namely; the command to fulfill the mandate, the command to be fair in establishing the law, the command to obey the leaders in good matters, and the command to return to the Qur'an and Sunnah when in dispute.